Study on the skin structure, hair follicle cycle, and GSDMA protein expression in Ganxi goats - Yang, Xue; Ji, Dengxiang; Wen, Caiyan; Chen, He; Jin, Zhangyong; He, Luyun; Zheng, Lucheng; Liu, Ben; Fan, Qingcan; Hu, Wei; Zheng, Wenya; Wang, Qianqian; et al. (Frontiers in Veterinary Science, 2025)
IntroductionThe Ganxi goat, a native Chinese breed inhabiting the hot and humid regions of western Jiangxi Province, displays notable adaptability to local climatic stress. This study aimed to investigate the morphological structure, hair follicle cycling pattern, and GSDMA protein expression in the skin of Ganxi goats, to elucidate the potential mechanisms underlying their environmental adaptation.MethodsUsing histological (H&E, Sacpic, and melanin staining), immunohistochemical (Ki67 and GSDMA), and Western blotting techniques, we conducted a year-long analysis of skin samples from ten 6-month-old female Ganxi goats.ResultsResults showed that total skin thickness ranged from 1,118 to 2088 μm, and epidermal thickness from 12 to 28 μm, with regional variation. Primary hair follicle depth averaged 1,056 μm. Hair follicle groups exhibited a typical trimeric structure, but were looser than in other goat breeds, with less-developed connective tissue sheaths, wider inter-follicular spaces, and well-developed sweat glands. Melanin was mainly localized in hair bulbs and outer root sheaths. Ki67-positive cells were concentrated in hair matrix regions. These structural features suggest that Ganxi goat skin is morphologically adapted to hot and humid environments. The secondary hair follicle cycle was divided into four phases: anagen (October–February), late anagen (March), catagen (April–August), and telogen (September). Ki67-positive cells were mainly located in the hair matrix, outer root sheath, and sebaceous glands, indicating active cell proliferation. Melanin was primarily distributed in the hair bulb and outer root sheath, but absent in the epidermis. GSDMA protein was cytoplasmically expressed in the epidermis, hair follicles, and sebaceous glands, with its level peaking in late anagen and decreasing through catagen and telogen phases.DiscussionThese findings highlight the structural and molecular adaptations of Ganxi goat skin to hot and humid environments and suggest that GSDMA may be involved in regulating the hair follicle cycle and maintaining skin homeostasis, and that further functional studies are required to establish a direct role in environmental adaptation.